2017
DOI: 10.1007/s10792-017-0594-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroid anti-inflammatory therapy suppresses the development of proliferative vitreoretinopathy more effectively than a steroid one

Abstract: COXs blocking during the development of PVR, overwhelming inflammation in the eye and reducing its consequences, is proved to be a much more effective and safe influence than the suppression of the entire cascade of arachidonic acid metabolism. Lornoxicam did not only improve the condition of the retina and the choroid but also significantly reduced the frequency of membrane formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…ConA is a lectin molecule well studied in the retinal tissue of both invertebrates and vertebrates [53] and used as an adhesive substrate for retinal cells in vitro [86]. Most recently, ConA was used to induce RPC migration from retinal grafts [87] as well as to suppress proliferative vitreoretinopathy in rats [88,89]. Both ConA and PLL have been used as in vitro substrates to examine survival of retinal neurons from amphibians, avians, invertebrates and mammals [86,90].…”
Section: Discussionmentioning
confidence: 99%
“…ConA is a lectin molecule well studied in the retinal tissue of both invertebrates and vertebrates [53] and used as an adhesive substrate for retinal cells in vitro [86]. Most recently, ConA was used to induce RPC migration from retinal grafts [87] as well as to suppress proliferative vitreoretinopathy in rats [88,89]. Both ConA and PLL have been used as in vitro substrates to examine survival of retinal neurons from amphibians, avians, invertebrates and mammals [86,90].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these observations have indicated that calcium-independent phospholipase A 2 was associated with the formation of PVR membranes, which might shed light on the treatment of PVR [80]. It is well known that steroid drugs can block the effect of phospholipase A 2 and inhibit the metabolism of arachidonic acid cascade [77].…”
Section: Other Mediators: Arachidonic Acid Metabolitementioning
confidence: 74%
“…Previous studies have confirmed that the expression COX-1 and COX-2 was detectable in the proliferative membranes of PVR patients [79]. At the early stages of PVR development, the administration of lornoxicam, known as nonsteroidal anti-inflammatory drugs (NSAIDs), could not only inhibit the expression of COXs in the retina and choroid, but also reduce the frequency of membrane formation by 31-43% in PVR models [77]. Recent reports have shown that calcium-independent phospholipase A 2 could regulate the proliferation of RPE cells and be identified in most transformed PRE cells in the membranes of PVR patients [80].…”
Section: Other Mediators: Arachidonic Acid Metabolitementioning
confidence: 91%
See 1 more Smart Citation
“…PVR is characterized by proliferation of cells and contraction of membranes within the vitreous cavity and on both sides of the retinal surfaces, which is a common cause of failure in rhegmatogenous retinal detachment surgery (Khan, Brady & Kaiser, 2015). Many attempts have been made in PVR pharmacotherapy (Abdullatif et al, 2018;Tikhonovich, Erdiakov & Gavrilova, 2018), but there are not ideal drugs for PVR treatment because the molecular mechanisms underlying PVR are not well understood. Pathogenesis of PVR is a complex biological process regulated by multiple growth factors and cytokines (Hoerster et al, 2017), and the retinal pigment epithelium (RPE) cells are considered as the key cell type in PVR, which is deemed to proliferate and migrate through retinal breaks (Umazume et al, 2014;Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%